Expression of DC-SIGN in human foreskin may facilitate sexual transmission of HIV - Soilleux, E J (Copyright 2004 Journal of Clinical Pathology, 2004)
This study demonstrates that the human immunodeficiency virus (HIV) binding C-type lectin DC-SIGN is coexpressed with CD4 and CCR5 on dendritic cells/macrophages in human foreskin. It is hypothesised that DC-SIGN may contribute to the sexual transmission of HIV in the foreskin, by enabling infection of permissive cells in cis and/or in trans.